PENGARUH KEMAMPUAN TEKNIK PEMAKAI, EFEKTIVITAS SIA, DUKUNGAN MANAJEMEN PUNCAK, LINGKUNGAN KERJA FISIK PADA KINERJA INDIVIDUAL - Widyasari, Harsya; Sadha Suardikha, I Made (E-Jurnal Akuntansi, 2015)
Good individual performance will help the company to achieve goals and meet the needs of the community. Accounting information system to facilitate the employees to do the work in the operational and financial activities. The purpose of this study was to determine the effect the ability of users of accounting information systems engineering, accounting information system effectiveness, top management support, and physical work environment on individual performance LPD in District Mengwi. Method of determining the sample in this study was done by using simple random sampling. Respondents in this study amounted to 59 employees in the District Mengwi LPD obtained by the formula Slovin. This study tested using multiple linear regression analysis with SPSS 15:00 for windows. Based on the results of the analysis can be concluded that the variable ability of users of accounting information systems engineering, accounting information system effectiveness, top management support, and physical work environment positive effect on individual performance.
Keywords: User Technical Ability, Effectiveness of Accounting Information Systems, Top Management Support, Physical Work Environment, Individual Performance